(untitled) (Per Musi, 2015)
This paper, Part 2 of the same study, presents the results of the experiment "Sensation of continuity of a musical excerpt" (CHAIB et. al. 2013) analyzed using the statistical technique Factor Analysis of Correspondences (FAC). The main objective of this analysis is to look through indexes, the influence of gesture in conveying sensations of continuity, suspension and conclusion on the performance on percussion. Once achieved the goal will be possible to generalize the results in performances conducted on the same lines presented in the experiment.